Physically based modelling techniques for landslide susceptibility analysis: A comparison. Issue 1 (1st June 2022) - Meena, V; Kumari, S; Shankar, V
Abstract: In mountainous areas, landslides are the most common natural catastrophic event, due to these events thousands of people are killed each year, and millions of dollars are lost in property damage. Landslides are mainly induced by earthquakes, rainfall, or manmade activities. Several GIS techniques, such as synthetic aperture radar, ranging data from spaceborne, airborne, and ground-based platforms, optical, and light detection and various physically based models such as SINMAP, TRIGRS, SHALSTAB etc. have been widely used to study slope failures in recent years. Each of these techniques has advantages and limitations for susceptibility analysis of landslides. The current research focuses on landslide susceptibility models that are physically based, their parameterization and working principle. The study infers that TRIGRS is the most commonly used model for slope stability analysis, whereas GEO top model is the only 3D slope stability model which considers the spatial variation of soil parameters hence it can be considered as the most advanced physically based slope stability model.